Using cereal science and technology for the benefit of consumers : proceedings of the 12th International ICC Cereal and Bread Congress 23-26 May, 2004, Harrogate, UK /: proceedings of the 12th International ICC Cereal and Bread Congress 23-26 May, 2004, Harrogate, UK. (2005) - Unknown
No abstract available